TikTok’s role in boosting motivation to learn Arabic among Malaysian university students - Sahrir, Muhammad Sabri; Usman, Nurul Ain; Muhammad Sharifuddin, Huda; Mohd Shamsul, Fatin Nasuha; Nor Azman, Nurfitrah Shahira (Perpustakaan Tun Abdul Razak, UiTM Negeri Sembilan, 2025)
This study investigates the impact of using the TikTok platform as a supplementary educational tool for enhancing motivation among university students in learning Arabic as a foreign language. The research responds to the increasing integration of social media in students' daily lives, particularly TikTok’s popularity among users aged 18–24, and explores how its features—short videos, interactivity, and entertainment—can be harnessed for pedagogical purposes.